Composting reduces the risks of resistome in beef cattle manure at the transcriptional level - Sun, Yuepeng; Staley, Zachery R.; Woodbury, Bryan; Riethoven, Jean-Jack; Li, Xu (Applied and environmental microbiology, 2024)
Proper treatment of manure before land application is essential to mitigate the spread of antibiotic resistance in the environment. Stockpiling and composting are two commonly used methods for manure treatment. However, the effectiveness of composting in reducing antibiotic resistance in manure has been debated. This work compared the ability of these two methods to reduce the risk of antibiotic resistance in beef cattle manure. Our results demonstrate that composting reduced more high-risk resistance genes at the transcriptomic level in cattle manure than conventional stockpiling. This finding not only underscores the effectiveness of composting in reducing antibiotic resistance in manure but also highlights the importance of employing RNA analyses alongside DNA analyses.